Exploring different perceptions of coach-athlete relationship : The case of Chinese Olympians - Li, B.; Dittmore, S. W.; Park, J.-A. (International Journal of Coaching Science, 2015)
The study aimed to investigate how Chinese Olympians` coach-athlete relationships differ from a convenience sample of Western Olympians within the context of the interpersonal constructs of Closeness, Co-orientation, and Complementary (three Cs). A total of 12 Olympians, including six Chinese Olympians and six Western Olympians, were invited to participate to this study. All participants had won medals at either World Championships or Olympic Games in their sports. A semi-structured interview was conducted with five open-ended questions about their coach-athlete relationships. Content analysis revealed Chinese Olympians have higher satisfaction than selected Western Olympians in terms of the commitment of coach and dedication of time of their coaches. Western athletes described the relationship as a partnership, but Chinese Olympians described the relationship as paternal. In addition, Chinese athletes were dominated in dyadic relationships since their personal lives were controlled by their coaches, while Western athletes were given more freedom and democracy by their coaches. With respect to gender, female athletes tended to train with male coaches but male athletes were more concerned with a coach`s knowledge rather than their gender. The study also indicated that athletes were more sensitive when they were in different gender coach-athlete relationships than in same gender relationships.